CHAMBER MUSIC INITIATIVE IN CHORAL SINGING AND ENSEMBLE WORK IN ERASMUS IP COOPERATION - MACZELKA, Noémi (Studia Universitatis Babes-Bolyai Musica, 2017)
Promoting chamber music initiative in the field of music education was regarded as priority of the Erasmus Intensive Program Chamber music initiative in choral singing and ensemble work based on compositions by Robert Schumann. Every European partner country in the consortium contributed individual suggestions and complements to develop students’ chamber musical creativity. At the end of the program participants represent program results in their final concert performances.